Pore-Scale Simulation of Water Flooding Using Volume of Fluid Method - Chuanqing Huang; Jiaosheng Zhang; Xuejiao Lu; Li Jihong; Yingsong Huang; Lijie Liu; Yajie Su; Jianguang Bai (Geofluids)
Water flooding is a commonly used method in oilfield development, and the water flooding process is essentially the process of oil-water movement in porous media. Pore-scale flow law in water flooding process can guide the oilfield development plan, to improve the oil recovery efficiency. In this paper, the computational domain is constructed from the CT scan images of real cores. The oil-water flow process of the water flooding in the pore structure is simulated using the interFoam solver in OpenFOAM. The influence of the displacement process and the distribution of the remaining oil is analyzed in three aspects: the water cut curve, the state of the same water injection amount, and the final displacement state. The flow rate velocity affects the water flooding swept range, and the recovery factor increases gradually with the increase of the flow rate. With different injection velocity, the sweeping sequence of pores is different, and the location and shape of remaining oil are very different. Due to the different dominant forces under different wettability states, the swept patterns of the core are also different.